Analysis on the influence of water pressure on the safety of karst tunnel lining structure. Issue 3 (May 2021) - Fei, Wan; Xuan, Zhang; Zhanqiang, Wang
Abstract: Tunnel lining structure in water-rich karst area bears random high water pressure, which seriously threatens the safety of lining structure. In order to determine the influence of water pressure on the safety of lining structure of karst tunnel, a numerical model of load-structure was established, and the safety factors of lining structure under different circumferential and longitudinal action ranges of water pressure were compared and analyzed. The calculation results show that the safety factor of arch and side wall of lining structure is the lowest when the circumferential action ranges of water pressure are 0.3S and S (S refers to the distance from vault to the maximum span). The safety reduction factor of lining structure is 0.4-1.0 when the longitudinal action range of water pressure is 4m-36m. The research results can provide a basis for designing lining structure of tunnels in water-rich karst stratum.